Impact of adhesive and photoactivation method on sealant integrity and polymer network formation - Borges, Boniek Castillo Dutra (2012)
We evaluated the influence of photoactivation method and hydrophobic resin (HR) application on the marginal and internal adaptation, hardness (KHN), and crosslink density (CLD) of a resin-based fissure sealant. Model fissures were created in bovine enamel fragments (n = 10) and sealed using one of the following protocols: no adhesive system + photoactivation of the sealant using continuous light (CL), no adhesive system + photoactivation of the sealant using the soft-start method (SS), HR + CL, or HR + SS. Marginal and internal gaps and KHN were assessed after storage in water for 24 h. The CLD was indirectly assessed by repeating the KHN measurement after 24 h of immersion in 100% ethanol. There was no difference among the samples with regard to marginal or internal adaptation. The KHN and CLD were similar for samples cured using either photoactivation method. Use of a hydrophobic resin prior to placement of fissure sealants and curing the sealant using the soft-start method may not provide any positive influence on integrity or crosslink density.